1973
DOI: 10.1111/j.1095-8649.1973.tb04481.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of five enzyme‐gene loci in four etheostomid species (Percidae: Pices) in an area of possible introgression

Abstract: The possibility of natural hybridization between two species of darters, Etheostoma spectubile and cueruleurn was investigated using the technique of starch gel electrophoresis of skeletal muscle homogenates. Inter-and intraspecific genetic variability at five enzyme loci was found. Resumed morphological hybrids are most probably not genetic hybrids as judged by their enzyme genotypes. The analysis of enzyme variability supports a previously published phylogeny for the darters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Using allozymes, Martin & Richmond (1973) found that presumed E. caeruleum  E. spectabile hybrids did not have genotypes consistent with a hybrid origin and suggested that F 1 hybrids must be rare in nature. Spawning occurred in laboratory experiments, in which F 1 hybrids were produced in tanks containing only reciprocal sexes of E. caeruleum and E. spectabile (Distler, 1968).…”
Section: Introductionmentioning
confidence: 98%
“…Using allozymes, Martin & Richmond (1973) found that presumed E. caeruleum  E. spectabile hybrids did not have genotypes consistent with a hybrid origin and suggested that F 1 hybrids must be rare in nature. Spawning occurred in laboratory experiments, in which F 1 hybrids were produced in tanks containing only reciprocal sexes of E. caeruleum and E. spectabile (Distler, 1968).…”
Section: Introductionmentioning
confidence: 98%
“…In tribute to their quality, only two published cases could be found where biochemical results contradict the conclusions drawn on the basis of morphological analyses. In Etheostomid (Percidae) species populations (Martin & Richmond, 1973;McLeod et al, 1980), morphologically intermediate individuals have not proven to be hybrids even though the species involved hybridize freely in the laboratory. Also, allozyme data were able to disallow the hybrid origin of the cyprinid species Rhinichfhys bowersi (Goldsborough & Clark) from R. micropogan and R. cataructae (Valenciennes) (Goodfellow et af., 1984).…”
Section: Hybridizationmentioning
confidence: 99%
“…471 trutta L.) and the Atlantic salmon (S. salur L.) in which the F, hybrids morphologically resemble one of the parents. An electrophoretic study of enzymes has been used to show that presumed hybrids between Etheostoma species are most probably not genetic hybrids (Martin & Richmond, 1973).…”
Section: Introductionmentioning
confidence: 99%